EFEKTIVITAS PEMBELAJARAN MATEMATIK MELALUI PENERAPAN PENDEKATAN SAINTIFIK SETTING KOOPERATIF PADA SISWA KELAS VII SMPIT UMAR BIN KHATTAB KABUPATEN PANGKEP - Ahmad Syamsuadi; Yusra Yusran (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This research is a type of pre-experimental research that aims to: Determine the level of competition for the effectiveness of students who are given a scientific approach to cooperative settings for quadrilateral and triangular flat fields in class VII students of SMP Negeri 6 Makassar based on (a) student achievement, (b) Activities student learning, and (c) Student response. The population in this study were all seventhgrade students of SMPIT Umar Bin Khattab Kabupaten Pangkep. While the sample was selected at random 1 class to be applied as a group that will be given learning treatment by applying a scientific approach to cooperative settings. Before learning is done, pre-test is given first, then learning is carried out by applying a scientific approach in a cooperative setting for 5 meetings, and then given a post-test. The results showed that: (1) the average score of learning implementation from the first meeting to the fifth meeting was 3.80 (very good category). (2) the average value of student learning achievement (gain) is 0.6 (medium classification). (3) the average score of the student activity category is 3.4 (very good category). (4) the average student response is 3.1 (the category tends to be positive). (5) The value of effectiveness (E) obtained is 3.20 (quite effective). Results Based on the research, the scientific approach of cooperative setting is quite effective to be applied to the seventh grade students of SMPIT Umar Bin Khattab Kabupaten Pangkep.